2016
DOI: 10.1063/1.4946827
|View full text |Cite
|
Sign up to set email alerts
|

Critical inclination for absolute/convective instability transition in inverted falling films

Abstract: 1Critical inclination for A/C transition in inverted falling films Liquid films flowing down the underside of inclined plates are subject to the interaction between the hydrodynamic and the Rayleigh-Taylor (R-T) instabilities causing a patterned and wavy topology at the free surface. The R-T instability results from the denser liquid film being located above a less dense ambient gas, and deforming into an array of droplets, which eventually drip if no saturation mechanism arises. Such saturation mechanism can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…promotes convective instability (spatial stability) of the flat film solution. Using a WIBL model, we obtain a minimum critical angle depending on the electric field strength, below which only convective instabilities occur, extending the findings in [38]. Comparisons with results for the full stability problem at zero Reynolds number are also provided.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…promotes convective instability (spatial stability) of the flat film solution. Using a WIBL model, we obtain a minimum critical angle depending on the electric field strength, below which only convective instabilities occur, extending the findings in [38]. Comparisons with results for the full stability problem at zero Reynolds number are also provided.…”
Section: Introductionsupporting
confidence: 76%
“…In the case that the curves of ω r (ξ) = 0 do not connect the points 0 and ξ c on R + , then the instability is absolute. The Briggs-Bers pinching criterion can then be applied to our problem -see [19,38] for its application to the non-electrified flow.…”
Section: Absolute and Convective Instabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…When inclining the solid substrate, the RTI is marginally modified for small slopes, but can be annihilated if the slope is large enough [14]. The distinction between these two regimes can be rationalized using an absolute/convective instability analysis [14,15]. Similarly, when the inclination of the substrate varies uniformly, i.e., the solid surface has a finite curvature, Trinh et al [5] showed that the Rayleigh-Taylor instability can be suppressed for a thin film if surface tension forces are strong enough.…”
Section: Introductionmentioning
confidence: 99%